A brief history of credit in UK higher education : laying siege to the ivory tower - Turnbull, Wayne (Great debates in higher education., 2020)
This timely book is the first to address the role of credit in UK higher education. It provides an overview and history of the development of credit in the UK HE sector and highlights how credit can be a vehicle for widening access and student choice, for curricular flexibility and mobility of learning.